Problemy implementacji podejścia procesowego opartego na normie ISO 9001:2000 - Kliciński, Sebastian (Problems with the Implementation of the Norm ISO 9001:2000 Based Process Approach, 2009)
In most Polish companies, the process approach is implemented through adaptation of management system to the ISO 9001:2000 standards. This process is both long and problematic. It has to be implemented because the way the Polish companies are run and managed must be adapted to the competition realities of the unified EU market. This paper presents experiences from the implementation of the norm ISO 9001:2000 based process approach in an industrial company. The problems and difficulties described in the article can serve as a basis for elaborations on rules and procedures of the process approach implementation in some future projects. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 58-66